MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) BERBANTUAN TEKA-TEKI SILANG TERHADAP MOTIVASI DAN HASIL BELAJAR IPAS SISWA KELAS IV - Dewi, Ketut Ella Ariseptiani Fournica Dewi; Agustiana, I Gusti Ayu Tri; Wirabrata, Dewa Gede Firstia (Pascasarjana Universitas Pendidikan Ganesha, 2025)
Elementary school students' motivation to learn and science learning outcomes remain relatively low due to conventional teaching approaches and limited student involvement in the learning process. This study aims to analyse the Team Games Tournament (TGT) model assisted by crossword puzzles on the motivation and learning outcomes of fourth-grade elementary school students in science. This study used a quantitative, quasi-experimental design with a non-equivalent post-test-only control group. The research subjects were 72 students. Data collection was conducted using a learning motivation questionnaire and a multiple-choice science learning outcomes test. Data were analysed using parametric statistical techniques, namely the t-test (independent sample t-test), after going through the prerequisite analysis tests in the form of normality and homogeneity tests. The results of the study show that the MANOVA analysis presented in Table 4.15 indicated that the significance values for each Pillai's Trace, Wilks' Lambda, Hotelling's Trace, and Roy's Largest Root were less than 0.05, so H0 was rejected. The study's conclusions indicate that the crossword-assisted TGT model significantly influences students' learning motivation and science learning outcomes. The implications of this study suggest that TGT-based learning supported by crossword puzzles can be an innovative alternative for improving the quality of science learning in elementary schools